1980
DOI: 10.1128/iai.30.1.135-139.1980
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion to virus-specific pre-early nuclear antigens in infants with primary cytomegalovirus infection

Abstract: Antibodies to human cytomegalovirus (CMV)-specific antigens were determined in sera serially collected from 10 infants with primary CMV infection. Antibodies to pre-early nuclear antigens (PENA), which are detectable in human embryonic lung cells within 3 h of CMV infection by anticomplement immunofluorescence staining, developed in all the patients. However, in contrast to the early response of anti-early antigens (EA), anti-late antigens (LA), and immunoglobulin M antimembrane antigens (MA), seroconversion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In human sera anti-CMV antibodies are mainly directed against CMV intracellular (nuclear and cytoplasmic) antigens (Fig. 1D), and the sera may contain only small amounts of antibodies with specificity for CMV-MA (2,5,13,15,16,26). Using human sera, we found that even mild fixation of CMV-infected cells prior to immunofluorescence causes considerable damage to the cell membranes, thereby making CMV intracellular (including nuclear) antigens accessible to their corresponding antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human sera anti-CMV antibodies are mainly directed against CMV intracellular (nuclear and cytoplasmic) antigens (Fig. 1D), and the sera may contain only small amounts of antibodies with specificity for CMV-MA (2,5,13,15,16,26). Using human sera, we found that even mild fixation of CMV-infected cells prior to immunofluorescence causes considerable damage to the cell membranes, thereby making CMV intracellular (including nuclear) antigens accessible to their corresponding antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, a convenient method is required that allows the analysis of multiple samples for the presence of antibodies with specificity for CMV-MA. Indirect immunofluorescence and immunoperoxidase staining of viable (1,3,5,13,16,17,22,23,26) or air-dried (8) CMV-infected cells have been used to measure antibody binding to CMV-MA. However, the specificity of the membrane staining reaction was not always reported (1,5,8,16,17).…”
mentioning
confidence: 99%
“…Antibodies against CMV-MA have been detected in sera from patients recovering from acute CMV infections (2,4,8,9,20). In contrast to neutralizing antibodies (10,14), CMV-MA antibodies are detectable only temporarily early after the onset of disease symptoms (2,8,20) and may help to limit viral replication by means of their capacity to mediate the killing of CMV-infected cells (2, 8; J. M. Middeldorp, J. Jongsma, and T. H. The, unpublished data).…”
mentioning
confidence: 99%